Implementation of PjBL-Based Teaching Media to Improve Learning Outcomes of Fourth Grade Elementary School Students - Mahrini, Mahrini; Novita, Rita; Rahmatullah, Rahmatullah; Sari, Siti Mayang (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study aims to describe the implementation of Project Based Learning (PJBL)-based teaching media to improve fourth-grade elementary students’ learning outcomes and examine their responses in thematic learning. The study was motivated by low student achievement and limited use of engaging, student-centered media. Using a qualitative case study approach, data were collected through observation, interviews, and documentation involving fourth-grade students at a public elementary school in Napai, Meulaboh, West Aceh. The developed teaching media included project-based student worksheets (LKPD), contextual learning videos, and group project guides, all validated by experts. The findings revealed that PJBL-based media created an active, enjoyable, and meaningful learning atmosphere. Students were fully engaged in stages such as identifying problems, designing, implementing, and presenting projects. Their responses were highly positive—they felt more interested, found the material easier to understand, and gained confidence in collaboration and problem-solving. Teachers noted improved classroom management and learning variety. Although requiring extra time and preparation, PJBL significantly enhanced student motivation and outcomes across cognitive, affective, and psychomotor domains. In conclusion, PJBL-based media effectively improved learning quality and outcomes, fostering active, independent, and meaningful learning experiences.